Participation and the environment - Tonci Tomic (CEPAL Review, 1992)
The petroleum-based production pattern has ultimately proved to be a dead end as the deteriorating quality of natural resources -owing to the way they have been used and appropriated- has begun to cast doubt upon the pattern’s viability. Repeated soundings of alarm on this score have increasingly sensitized the population, thus creating a level of ecological awareness that has moved society to voice its ever more vehement rejection of a system which bases itself on the destruction or degradation of natural resources and, in so doing, jeopardizes the sustainability of the development process.